Building a Comprehensive API Ecosystem for Non-profit Digital Analytics - Penta Rao Marapatla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive technical framework for integrating AI-driven analytics and API ecosystems in nonprofit organizations. The implementation combines advanced donor analytics with multi-platform data synchronization, enabling organizations to effectively leverage social media interactions, advertising metrics, and donor behavior patterns. The system architecture incorporates sophisticated machine learning models for predictive analytics, a distributed computing infrastructure for data processing, and robust API integrations across multiple platforms. Through token-based authentication systems and automated workflow management, the framework ensures secure and efficient data handling while maintaining scalability. The implementation significantly improves donor retention, operational efficiency, and engagement metrics, providing nonprofits with powerful tools for data-driven decision-making.
Keywords: Nonprofit Digital Analytics; API Integration Architecture; Donor Management Systems; Machine Learning Analytics; Data Synchronization Framework